Impacts of soil water stress on the acclimated stomatal limitation of photosynthesis: Insights from stable carbon isotope data - Aliénor Lavergne; David Sandoval; Vincent J. Hare; Heather Graven; Iain Colin Prentice (Global Change Biology, 2020)
Atmospheric aridity and drought both influence physiological function in plant leaves, but their relative contributions to changes in the ratio of leaf internal to ambient partial pressure of CO 2 ( χ ) – an index of adjustments in both stomatal conductance and photosynthetic rate to environmental conditions – are difficult to disentangle. Many stomatal models predicting χ include the influence of only one of these drivers. In particular, the least‐cost optimality hypothesis considers the effect of atmospheric demand for water on χ but does not predict how soils with reduced water further influence χ , potentially leading to an overestimation of χ under dry conditions. Here, we use a large network of stable carbon isotope measurements in C 3 woody plants to examine the acclimated response of χ to soil water stress. We estimate the ratio of cost factors for carboxylation and transpiration ( β ) expected from the theory to explain the variance in the data, and investigate the responses of β (and thus χ ) to soil water content and suction across seed plant groups, leaf phenological types and regions. Overall, β decreases linearly with soil drying, implying that the cost of water transport along the soil–plant–atmosphere continuum increases as water available in the soil decreases. However, despite contrasting hydraulic strategies, the stomatal responses of angiosperms and gymnosperms to soil water tend to converge, consistent with the optimality theory. The prediction of β as a simple, empirical function of soil water significantly improves χ predictions by up to 6.3 ± 2.3% (mean ± SD of adjusted‐ R 2 ) over 1980–2018 and results in a reduction of around 2% of mean χ values across the globe. Our results highlight the importance of soil water status on stomatal functions and plant water‐use efficiency, and suggest the implementation of trait‐based hydraulic functions into the model to account for soil water stress.